Systematic review of extraction techniques and environmental future prospects for the Commiphora Gileadensis medicinal plant - Aiman A., Mokaizh; Nour, Abdurahman Hamid; Rosli, Mohd Yunus; Elnour, Ahmed Adam Hassan Mohammed (Tamkang University, 2024)
Commiphora gileadensis is a significant medicinal plant with various therapeutic uses. The plant’s phytoconstituents possess antioxidant, antibacterial, cytotoxic, anticancer, and antiviral properties, which recently attracted research interest. The objectives are as follows: (i) this study serves as the first Systematic Literature Review (SLR) on C. gileadensis that identified the used extraction methods to extract the bioactive components of C. gileadensis; (ii) outlined the literature study gap and stated the future trends’ recommendations. The existing literature on C. gileadensis was searched on Scopus, PubMed, and Web of Science. This PRISMA-style article searches covered articles published between 2010 to 2022. The search was conducted using common terms like "Commiphora gileadensis," "Balm of Gilead," "Balm of Judea," "Apharsemon," "Opobalsamum," and "Becham". The search on the three databases yielded 156 documents, 55 of which were included. The SLR study found low extraction yields and phenolic contents of the phytochemical components of C. gileadensis due to ineffective extraction techniques and process parameters. More so, these might involve environmental implications for how resources are used, how much energy is consumed, and how much waste is produced throughout the extraction process. The SLR overcame the limitations of traditional extraction methods and boosted phenolic content recovery by using eco-friendly technique such as Microwave-Assisted Extraction (MAE). It also recommended researching how improved extraction methods affect the phytochemical composition and recovery yield of the extracts.